Differential expression of plasma microRNA‐125b in hepatitis B virus‐related liver diseases and diagnostic potential for hepatitis B virus‐induced hepatocellular carcinoma. Issue 4 (28th May 2016) - Chen, Shanshan; Chen, Hao; Gao, Shanshan; Qiu, Shili; Zhou, Hu; Yu, Mingxia; Tu, Jiancheng
Abstract : Aim : Acting as a tumor suppressor, microRNA (miR)‐125b shows aberrant low expression in hepatocellular carcinoma (HCC), and researchers have found that its dysregulation has a close relationship with hepatitis B virus (HBV) infection. Here, we investigated the expression profile of this miRNA in the plasma of healthy subjects and patients with chronic HBV‐related liver diseases in order to confirm the feasibility of this circulating miRNA as a differential diagnostic biomarker for HBV‐induced HCC (HBV‐HCC). Methods : A total of 242 individuals were enrolled in this study. The expression levels of plasma miR‐125b were examined using quantitative real‐time polymerase chain reaction technology. Results : The levels of plasma miR‐125b were remarkably decreased in HBV‐HCC patients compared to healthy controls and HBV subjects without HCC (all P  < 0.001), and the low plasma miR‐125b levels in HBV‐HCC patients were associated with higher prevalence of metastasis ( P  = 0.021). The receiver–operating characteristic curve analyses indicated that plasma miR‐125b presented a high accuracy (area under the curve = 0.891, 0.958, 0.958) for diagnosing HBV‐HCC cases from healthy controls and patients with chronic hepatitis B and HBV‐related liver cirrhosis, respectively. In addition, our study found that the expression levels of plasma miR‐125b in HBV patients without HCC were higher than those in healthy subjects ( P  < 0.001); it yielded an area under the curve of 0.691 in discriminating patients with chronic HBV infection who were negative for HCC from healthy controls. Conclusion : The measurement of plasma‐based miR‐125b holds promise as a diagnostic marker for HBV‐HCC differential diagnosis and for chronic HBV viral infection. Those HBV‐infected individuals with increased risk of HCC would be detected early through monitoring the changes in this circulating miRNA.